2021
DOI: 10.33785/ijds.2021.v74i01.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and characterization of functional chocolate with addition of butter fruit milkshake powder as a source of phenolic, flavonoid and carotenoid

Abstract: Butter fruit milkshake powder (BFMS) is a healthful mixture of avocado pulp and dairy components with high nutritional and antioxidant activity. In this study, an attempt has been made to enhance the nutraceutical and functional properties of the chocolate with BFMS powder at the 15-60% level based on the physical, nutritional, sensory attributes, and storage of study. Sensory studies of chocolate indicated that maximum sensory score was found at 30% incorporation of BFMS without adverse effects. BFMS powder's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the other hand, sugar content analysis revealed that lyophilized fruits such as grapes are suitable sugar substitutes in the formulation. Based on Kumari et al (2021), as a source of phenolic, flavonoid, and carotenoid compounds, butter fruit milkshake powder, a nutritious blend of avocado pulp and dairy ingredients with high nutritional and antioxidant activity, was added to functional chocolate at a level of 30%. They said that the formulation of the chocolate now had more of the minerals Ca, Mg, Fe, Zn, and Mn.…”
Section: Fortified Cho Col Ate Smentioning
confidence: 99%
“…On the other hand, sugar content analysis revealed that lyophilized fruits such as grapes are suitable sugar substitutes in the formulation. Based on Kumari et al (2021), as a source of phenolic, flavonoid, and carotenoid compounds, butter fruit milkshake powder, a nutritious blend of avocado pulp and dairy ingredients with high nutritional and antioxidant activity, was added to functional chocolate at a level of 30%. They said that the formulation of the chocolate now had more of the minerals Ca, Mg, Fe, Zn, and Mn.…”
Section: Fortified Cho Col Ate Smentioning
confidence: 99%